CLINICAL SUCCESS STORY OF MANAGEMENT OF VIRAL ENCEPHALITIS SEQUEL THROUGH AYURVEDIC PRINCIPLES - Pradeep Agnihotri; Prashanth A S (International Journal of Applied Ayurved Research, 2015)
Viral encephalitis sequel is very difficult to be managed and patients some time may need rehabilitation depending upon the extent of damage caused in the brain tissue. This is often called as Acquired Brain Injury. The sufferer usually ends up with either blindness if optic nerve is involved or deafness if auditory nerve is involved. Fewer hopes are available in the modern medicine to treat secondary optic nerve atrophy to regenerate or remyelinate the affected nerve. Very often it is said that over the period of treatment it may regain its function, but not for sure.